Cognitive motivation among Wasit University professors - Dr . Mayada Jumaa Hassan (Journal of College of Education, 2023)
The study aimed to identify the level of cognitive motivation among students of professors at the University of Wasit, as well as to know the significance of statistical differences in cognitive motivation according to the variables of gender (males - females), length of service, and academic specialization (scientific, humanities) on cognitive motivation. The random research sample was (200) professors. As for the research tool used by the researcher, it was built to measure the cognitive motivation of the professor at Wasit University, after making some modifications to it to extract validity and reliability. It was applied to the basic research sample in the second semester of the academic year (2022 - 2023 AD), which was (200) male and female professors. . The most important statistical methods that were applied in the study are (arithmetic mean and weighted weight). The most important results of the study are: the emergence of a high level of cognitive motivation in general There was also an effect of the academic specialization variable on cognitive motivation in favor of scientific specialization, while the gender variable had no effect on the cognitive motivation of male and female professors. The study concluded with a number of recommendations and proposals: the most important of which is the need for the responsible educational authorities to contribute to the process of investing in the high cognitive motivation of teachers in a way that contributes to stimulating scientific activities, university participation and competitions in this field, which contributes to achieving scientific and academic progress to reach cases of excellence and creativity in the field of science and knowledge.